The role of Zakat in achieving economic empowerment, environmental sustainability and social re-engineering as promoted in the 12th Malaysia plan (12MP) - Mahadi, Nur Farhah; Mohd. Zain, Nor Razinah; Othman, Anwar Hasan Abdullah (2020)
This study seeks to gain a deeper understanding on the role of zakᾱt in achieving economic empowerment, environmental sustainability and social re-engineering as promoted in the 12th Malaysia Plan (12 MP) which aligned with Shared Prosperity Vision 2030 (SPV2030) as well as United Nation’s Sustainable Development Goals (SDGs) to provide support to fulfil the Maqᾱṣid al-Sharῑ῾ah. This study uses the library study method. Among the reading materials that have been referred include those materials related to the role of zakᾱt, the government five-year development plan namely 12th Malaysia Plan from 2021 - 2025, the Shared Prosperity Vision 2030 (SPV2030), SDGs and Maqᾱṣid al-Sharῑ῾ah. Qualitative approach is used in this study to collect information, documents and data accordingly with regard to the topic discussed. Results: By understanding the importance of zakᾱt in achieving economic empowerment, environmental sustainability and social re-engineering, we can further enhance the distribution and utilisation of these zakᾱt funds to ensure its positive impact in socio-economic. Eventually, this may also motivate the State Islamic Religious Council (SIRC) to promote the importance of fair and equitable distribution of zakᾱt to aṣnᾱf. The study will provide significant socio-economic impacts as the results will enable new initiatives by industries to develop better management of zakᾱt funds to finally achieve the economic empowerment, environmental sustainability and social reengineering in the society as promoted in the 12th Malaysia Plan (12 MP) which aligned with Shared Prosperity Vision 2030 (SPV2030) as well as United Nation’s Sustainable Development Goals (SDGs) to provide support to fulfil the Maqᾱṣid al-Sharῑ῾ah.